Antibiotics and mental health: The good, the bad and the ugly. (12th July 2022) - Dinan, Katherine; Dinan, Timothy
Abstract: Antibiotics are recognised as, on occasion, producing psychiatric side effects, most notably depression and anxiety. Apart from antimicrobial activity, antibiotics have multiple off‐target effects. The brain–gut–microbiota axis has multiple sites for off‐target activity, which may produce either positive or negative antibiotic effects. Here we review how antibiotics impact mental health by acting through the brain–gut–microbiota axis. Microbes in the gut influence brain function by acting through the vagus nerve or by altering the production of short‐chain fatty acids or the amino acid tryptophan, the building block of serotonin. Not all antimicrobial actions of antibiotics have a negative impact. The first antidepressant discovered was actually an antibiotic: isoniazid is an antibacterial drug developed for treating tuberculosis. Minocycline, which enters the brain and mediates its effects through microglia, shows antidepressant activity. Some antibiotics bring about a significant decrease in gut microbial diversity, and this is viewed as a risk factor for depression. Other risk factors induced by antibiotics include altered gut barrier function, activation of the hypothalamic–pituitary–adrenal axis, reducing levels of brain‐derived neurotrophic factor or oxytocin and alteration of vagal tone. Although most patients taking antibiotics do not suffer from an iatrogenic psychiatric disorder, some do. As clinicians, we need to keep this in mind. The development of new antibiotics is primarily focused on antibiotic resistance, but efforts should be made to reduce off‐target brain–gut–microbiota effects resulting in mental health problems. Abstract :